Political Emigration and Postal Surveillance in Socialist Slovenia - Drnovšek, Marjan (Two Homelands, 2010)
The paper deals with the attitude of socialist Slovenia towards political emigrants using archival materials from the Republic Secretariat for Internal Affairs in Ljubljana. The basic materials are microfilms of the annual reports of the Slovenian State Security Service, which were sent to the Federal Secretariat for Internal Affairs in Belgrade. The majority of the archival materials have been sent to the Archive of the Republic of Slovenia and are available to the public. Using a historical approach and time and content sampling methods, the author analyses the individual reports and places them into a wider historical context. His intent is to bring attention to the absurd amount of surveillance of people and postal parcels conducted during the socialist period. It is difficult to compare the Slovenian and/or Yugoslavian operations in the area of state security with those of e.g. the Stasi in East Germany and other state security forces in eastern European countries before the fall of the Berlin Wall, but we do find examples of similar operations, particularly during the period of greater influence of the Soviet Union immediately after the Second World War. A significant part of the paper discusses the attitude of the State Security Service towards Slovenian political emigrants around the world.